Native language interference in English adjective ordering: A study of senior secondary school students in Nigeria - Nasiru Bello, Abubakar; Isyaku, Hassan; Normah, Yusof; Akmah, Yusof (2017)
Many studies revealed that non-native speakers of English language face difficulties in understanding the correct order of adjectives, especially when there is more than one adjective qualifying a noun. This is a case of interference which, although criticized by several authors, referring to the influence of one language on another. This study aims to examine native language interference in English adjective position and order among English non-native speakers. The study employed a qualitative approach, in which test and error analysis were used to collect and analyze data respectively. The participants comprised final year students of Government Secondary School Dala, Kano-Nigeria. A sample of 20 students who are Hausa native speakers was purposively selected using typical sampling strategy. The findings revealed that the students’ native language influences their English adjective position and order. Altogether, the students made 66 errors out of 200 responses they provided across English adjective position and order. These errors might reflect poor academic performance amongst the students. Therefore, the students should develop both English speaking, and reading culture and their teachers should encourage them, since language learning requires constant practice.